Consumable friction plug welding of TC4 plate: parameters, microstructures, and mechanical properties. (27th September 2019) - Li, Junping; Shen, Yifu; Yan, Yinfei; Tang, Jingming; Hou, Wentao; Huang, Guoqiang; Liu, Wenming
Abstract: In this paper, a technique of consumable friction plug welding (CFPW) was introduced in the welding of TC4 plate for repairing the keyhole and defects. A semi-consumable friction head composed of a nickel base super-alloy clamping shoulder and a titanium alloy plug was designed. Several defect-free welded samples have been obtained and the process window of CFPW for TC4 plate has been explored. The process window of CFPW for TC4 alloy was very narrow. The cross sections of CFPW joint were divided into five zones with different microstructure. The final microstructure in the thermal deformation (TD) zone was refined. The ultimate tensile strength and elongation of the CFPW samples were both up to 85% of the base metal, and the base heat affected (BHA) zone was a weak region in the joint. The hardness fluctuation of joint cross section was closely related to the change of microstructure in different welding zones